Нормування праці як невідємна складова організаційно-економічного механізму управління персоналом будівельного підпрємства - Шевчук, К. І. (Ways to Improve Construction Efficiency, 2013)
The historical development of valuation work as a science is considered. The analysis of regulatory methods, organizational support and state regulation of labor in construction isana lyred.